ChemInform Abstract: Effective Palladium‐Catalyzed Synthesis of Triarylethene‐Based Molecules in Aqueous Solution. Issue 9 (5th March 2013) - Zhu, Yan; Sun, Peng; Yang, Hailong; Lu, Linhua; Yan, Hong; Creus, Marc; Mao, Jincheng
Abstract The one‐step double Suzuki—Miyaura coupling reaction of 2‐aryl‐1, 1‐dibromo‐1‐alkenes with aryl/heteroarylboronic acids proceeds under ligand‐, additive‐, and inert‐gas‐free conditions using aqueous PEG as solvent.